2008
DOI: 10.1016/j.hrthm.2008.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Common ß-adrenergic receptor polymorphisms are not associated with risk of sudden cardiac death in patients with coronary artery disease

Abstract: Background-Previous studies suggest β adrenergic receptor (βAR) single nucleotide polymorphisms (SNPs) are associated with out-of-hospital sudden cardiac death (SCD) and overall mortality, but did not specifically examine risk of ventricular arrhythmias (VA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Case-control studies reported no association between this polymorphism and the above-mentioned phenotypic outcomes [46,47]. Although these case-control studies have relatively large sample sizes (495–5393), they may have been confounded by unmeasured factors.…”
Section: Adrb2: Arg16gly; 285a >G (Rs1042713)mentioning
confidence: 99%
See 1 more Smart Citation
“…Case-control studies reported no association between this polymorphism and the above-mentioned phenotypic outcomes [46,47]. Although these case-control studies have relatively large sample sizes (495–5393), they may have been confounded by unmeasured factors.…”
Section: Adrb2: Arg16gly; 285a >G (Rs1042713)mentioning
confidence: 99%
“…The polymorphism encoding the Gln27Glu change was not associated with the increased risk of sudden cardiac death and ventricular arrhythmias in patients with coronary artery disease [46], nor is it associated with the risk of MI or ischemic stroke in patients who were pharmacologically treated for hypertension [47]. The polymorphism has also been studied in heart failure.…”
Section: Adrb2: Gln27glu; 318c >G (Rs1042714)mentioning
confidence: 99%
“…Specifically, several prior study populations in which no associations or weak associations between ADRB2 and sudden cardiac arrest were identified were recruited from populations that were already in clinical care 17 or were healthcare professionals. 15 By contrast, the Cardiovascular Health Study, where a strong positive association was observed, was a population-based sample.…”
Section: Discussionmentioning
confidence: 99%
“…14 We note, however, that these prior studies included other population differences, including prevalence of known coronary artery disease, and measurement differences, including sudden cardiac arrest identification, that may also explain the inconsistent findings. 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation